2016
DOI: 10.3390/ijms17101612
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of Calpain-4 Predicts Poor Prognosis in Patients with Gastric Cancer after Gastrectomy

Abstract: Calpain-4 belongs to the calpain family of calcium-dependent cysteine proteases, and functions as a small regulatory subunit of the calpains. Recent evidence indicates that calpain-4 plays critical roles in tumor migration and invasion. However, the roles of calpain-4 in gastric tumorigenesis remain poorly understood. Herein, we examined calpain-4 expression by immunohistochemical staining on tissue microarrays containing tumor samples of 174 gastric cancer patients between 2004 and 2008 at a single center. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…However, the potential value of Capn4 protein as a biomarker to predict clinical outcomes is still debatable. For example, Wu et al [10] reported that elevated expression of Capn4 was linked to poor prognosis as well as lymph node metastasis and deeper tumor invasion in esophageal cancer, which was consistent with the results in nasopharyngeal carcinoma [12], but no significant association was found between Capn4 protein expression and T stage in gastric cancer [13]. And Cheng et al [9] found that there was a significant relationship between Capn4 protein expression and TNM staging; however, in non-small cell lung cancer, no significant correlation was observed between Capn4 expression and tumor stage [14].…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…However, the potential value of Capn4 protein as a biomarker to predict clinical outcomes is still debatable. For example, Wu et al [10] reported that elevated expression of Capn4 was linked to poor prognosis as well as lymph node metastasis and deeper tumor invasion in esophageal cancer, which was consistent with the results in nasopharyngeal carcinoma [12], but no significant association was found between Capn4 protein expression and T stage in gastric cancer [13]. And Cheng et al [9] found that there was a significant relationship between Capn4 protein expression and TNM staging; however, in non-small cell lung cancer, no significant correlation was observed between Capn4 expression and tumor stage [14].…”
Section: Introductionsupporting
confidence: 67%
“…What is more important, it is reported that Capn4 is involved in tumor progression through many pathways, such as epithelial-mesenchymal transition (EMT), the FAK-Src signaling pathways, the Wnt/ -catenin ( -catenin), and the nuclear factor B (NF-B) signaling pathways [24,[30][31][32]. Additionally, Capn4 also correlates with drug response and tumor resistance and might serve as a potential therapeutic target for several kinds of tumors [13,14,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, NF‐κB RelA/p65 enhances methylation of CpG islands on the promoter region and represses the transcription of certain tumor‐suppressor genes through recruitment of DNA methyltransferase‐1 (DNMT1) . Moreover, calpain proteins, a family of intracellular Ca2 ± dependent cysteine proteases are associated with the development and progression of a variety of tumors, such as breast cancer, gastric cancer . There is still controversy in the expression pattern of calpain in PCa samples due to the contradictory results of mRNA .…”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, calpain proteins, a family of intracellular Ca2 ± dependent cysteine proteases are associated with the development and progression of a variety of tumors, such as breast cancer, 10 gastric cancer. 11,12 There is still controversy in the expression pattern of calpain in PCa samples due to the contradictory results of mRNA. 13,14 In the previous study, we confirmed that calpain-2 also cleaves CRMP4, 15 but the functional modulation remains unclear.…”
mentioning
confidence: 99%